Inhibition of Immune Complex Complement Activation and Neutrophil Extracellular Trap Formation by Peptide Inhibitor of Complement C1 - Hair, Pamela S.; Enos, Adrianne I.; Krishna, Neel K.; Cunnion, Kenji M. (Frontiers in Immunology, 2018)
Two major aspects of Systemic Lupus Erythematosus (SLE) pathogenesis that have yet to be targeted therapeutically are immune complex-initiated complement activation and neutrophil extracellular trap (NET) formation by neutrophils. Here we report in vitro testing of Peptide Inhibitor of Complement C1 (PIC1) in assays of immune complex-mediated complement activation in human sera and assays for NET formation by human neutrophils. The lead PIC1 derivative, PA-dPEG24, was able to dose-dependently inhibit complement activation initiated by multiple types of immune complexes, including C1-antiC1q immune complexes, limiting the generation of pro-inflammatory complement effectors including C5a and membrane attack complex (sC5b-9). In several instances PA-dPEG24 achieved complete inhibition with complement effector levels equivalent to background. PA-dPEG24 was also able to dose-dependently inhibit NET formation by human neutrophils stimulated by PMA, MPO or immune complex activated human sera. In several instances PA-dPEG24 achieved complete inhibition with NETosis with quantitation equivalent to background levels. These results suggest that PA-dPEG24 inhibition of NETs occurs by blocking the MPO pathway of NET formation. Together these results demonstrate that PA-dPEG24 can inhibit immune complex activation of the complement system and NET formation. This provides proof of concept that peptides can potentially be developed to inhibit these two important contributors to rheumatologic pathology that are currently untargeted by available therapies.